Surface Plasmon Resonance Analysis Shows an IgG-Isotype-Specific Defect in ABO Blood Group Antibody Formation in Patients with Common Variable Immunodeficiency - Fischer, Michael B.; Wolfram, Wendelin; Binder, Christoph J.; Böhmig, Georg A.; Wahrmann, Markus; Eibl, Martha M.; Wolf, Hermann M. (Frontiers in Immunology, 2015)
Background: Common variable immunodeficiency (CVID) is the most common clinically severe primary immunodeficiency and comprises a heterogeneous group of patients with recurrent severe bacterial infections due to the failure to produce IgG antibodies after exposure to infectious agents and immunization. Diagnostic recommendations for antibody failure include assessment of isoagglutinins. We have readdressed this four decades old but still accepted recommendation with up to date methodology. Methods: Anti-A/B IgM- and IgG-antibodies were measured by Diamed-ID Micro Typing, surface plasmon resonance (SPR) using the Biacore® device and flow cytometry. Results: When Diamed-ID Micro Typing was used, CVID patients (n=34) showed IgG- and IgM-isoagglutinins that were comparable to healthy volunteers (n=28), while all XLA patients (n=8) had none. Anti-A/B IgM-antibodies were present in more than 2/3 of the CVID patients and showed binding kinetics comparable to anti-A/B IgM-antibodies from healthy individuals. A correlation could be found in CVID patients between levels of anti-A/B IgM-antibodies and levels of serum IgM and PnP-IgM-antibodies. In contrast in CVID patients as a group ABO antibodies were significantly decreased when assessed by SPR, which correlated with levels of switched memory, non-switched memory and naïve B cells, but all CVID patients had low/undetectable anti-A/B IgG-antibodies. Conclusion: These results indicate that conventional isoagglutinin assessment and assessment of anti-A/B IgM antibodies are not suited for the diagnosis of impaired antibody production in CVID. Examination of anti-A/B IgG antibodies by SPR provides a useful method for the diagnosis of IgG antibody failure in all CVID patients studied, thus indicating an important additional rationale to start immunoglobulin replacement therapy early in these patients, before post-infectious sequelae develop.